A reversal of the shift towards earlier spring phenology in several Mediterranean reptiles and amphibians during the 1998–2013 warming slowdown. (1st September 2017) - Prodon, Roger; Geniez, Philippe; Cheylan, Marc; Devers, Florence; Chuine, Isabelle; Besnard, Aurelien
Abstract: Herps, especially amphibians, are particularly susceptible to climate change, as temperature tightly controls many parameters of their biological cycle—above all, their phenology. The timing of herps' activity or migration period—in particular the dates of their first appearance in spring and first breeding—and the shift to earlier dates in response to warming since the last quarter of the 20 th century has often been described up to now as a nearly monotonic trend towards earlier phenological events. In this study, we used citizen science data opportunistically collected on reptiles and amphibians in the northern Mediterranean basin over a period of 32 years to explore temporal variations in herp phenology. For 17 common species, we measured shifts in the date of the species' first spring appearance—which may be the result of current changes in climate—and regressed the first appearance date against temperatures and precipitations. Our results confirmed the expected overall trend towards earlier first spring appearances from 1983 to 1997, and show that the first appearance date of both reptiles and amphibians fits well with the temperature in late winter. However, the trend towards earlier dates was stopped or even reversed in most species between 1998 and 2013. We interpret this reversal as a response to cooling related to the North Atlantic Oscillation (NAO) in the late winter and early spring. During the positive NAO episodes, for certain species only (mainly amphibians), the effect of a warm weather, which tends to advance the phenology, seems to be counterbalanced by the adverse effects of the relative dryness. Abstract : The date of first appearance in spring of the Mediterranean snake Malpolon monspellulanus shifted about 55 days earlier from 1983 to 1997, but this trend was reversed afterwards. This shift, that was observed in several amphibian and reptile species, mirrors the temperature changes in the February–March period, in relation with the North Atlantic Oscillation.